2018
DOI: 10.26582/k.50.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barefoot and minimally shod footwear on effective mass – implications for transient musculoskeletal loading

Abstract: The purpose of this investigation was to explore the effects of barefoot and minimally shod footwear on effective mass, and determine the implications that this has for transient loading during running. Fifteen male runners ran at 4.0 m/s in five different footwear conditions (barefoot, running trainer, Nike-free, Inov-8 and Vibram five-fingers). Kinematics were collected using an 8 camera motion capture system and ground reaction forces via an embedded force platform. Effective mass was examined using impulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…It was also revealed using SPM that medial tibiofemoral loading was greater during early stance yet via discrete analyses that the lateral tibiofemoral integral was greater in minimal compared to both maximal and traditional running shoes. This observation supports those of Sinclair et al (2018) who showed via SPM and the discrete knee adduction moment, that minimal footwear enhanced the extent of medial knee loading compared to traditional running shoes although there has yet to be any investigation comparing lateral tibiofemoral loading in minimal, maximal and traditional running shoes. Therefore, as the aetiology of degenerative hip and tibiofemoral joint pathologies are influenced by compressive joint loading (Johnson & Hunter, 2014), it is possible that minimal footwear may enhance the risk of chronic hip and medial tibiofemoral pathologies.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It was also revealed using SPM that medial tibiofemoral loading was greater during early stance yet via discrete analyses that the lateral tibiofemoral integral was greater in minimal compared to both maximal and traditional running shoes. This observation supports those of Sinclair et al (2018) who showed via SPM and the discrete knee adduction moment, that minimal footwear enhanced the extent of medial knee loading compared to traditional running shoes although there has yet to be any investigation comparing lateral tibiofemoral loading in minimal, maximal and traditional running shoes. Therefore, as the aetiology of degenerative hip and tibiofemoral joint pathologies are influenced by compressive joint loading (Johnson & Hunter, 2014), it is possible that minimal footwear may enhance the risk of chronic hip and medial tibiofemoral pathologies.…”
Section: Discussionsupporting
confidence: 88%
“…The impact peak was defined in the maximal and traditional running shoes as the first peak in vertical GRF. In the minimal footwear where there was not a consistent impact peak, according to the protocols of Lieberman et al (2010) and Sinclair et al (2018), we defined the position of the impact peak at the same relative position as in the maximal and traditional running shoes. The time to impact peak (D time) was quantified as the duration from footstrike to impact peak.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations